Peripheral complement C4 protein in schizophrenia: Association with gene copy number and immune cell subtypes - Agnieszka Kalinowski; Claudia Macaubas; Hanmin Guo; Lauren A. Anker; Diane E. Wakeham; Marcus Ho; Reenal Pattni; Batuhan Bayram; Surbhi Sharma; Joanna Liliental; Jong H. Yoon; Elizabeth D. Mellins; et al. (Proceedings of the National Academy of Sciences, 2026)
The lack of highly effective disease-modifying treatments for schizophrenia necessitates exploration of novel aspects of its pathophysiology, including attention to innate immune mechanisms outside the brain. C4 protein activation, associated with the complement cascade of innate immunity, associates with symptoms and predicts outcomes in schizophrenia. However, C4 protein activation does not coincide with expected changes to other proteins in the complement cascade, suggesting another source of C4 protein activation. Studying a combination of fresh whole blood from 10 anonymous donors and a large set of publicly available microarray data, we show that C4 protein is found and expressed primarily in neutrophils and monocytes. Then, we compared the correlation between C4 protein in neutrophils, classical monocytes, plasma, and the number of C4A gene copies. We determined the number of C4A genes using digital droplet PCR, C4 protein in neutrophils (15 patients/21 controls) and plasma (30 patients/38 controls) using Western blotting, and classical monocytes (30 patients/38 controls) using flow cytometry. We found a large positive correlation between the number of C4A gene copies and the amount of C4 protein only in neutrophils and only in the schizophrenia group (Spearman’s rho = 0.63, 95% BCa CI: 0.12 to 0.89, P = 0.012). Our results indicate a convergence of innate immunity mechanisms associated with schizophrenia. The involvement of innate immunity deserves further attention to determine whether it could be a target for therapy in schizophrenia.